2021
DOI: 10.24926/ijps.v8i1.3687
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Interdisciplinary Collaboration: A Study of Enablers and Inhibitors Across Silos in Higher Education

Abstract: Within UK Higher Education Institutions (HEIs) there is evidence of limited interdisciplinary communication and engagement (Macfarlane, 2006). The focus on discipline-based working practices has created a lack of awareness regarding research taking place elsewhere that may overlap with or bolster work being undertaken by the researcher (Bess & Dee, 2012). Teams that work across discipline-based boundaries acknowledge their differences and work to build trust through finding the strengths in researcher diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is suggested that Kezar's [3] seven organizational features are vital for recognizing which structures and supports are needed to carry out SD work and be better prepared to meet the demands being placed on HEIs today. These structural components are augmented by other studies that outline best practice approaches, which can be implemented within a HEI to increase interdisciplinary collaboration [70]. Future research should include understanding the relationship between ecological legacy and collaborative cultures, and the correlation of the eight categories of SD within HEIs with the infrastructure offered by Kezar [3] and Roper [70] in order to offer more concrete ways of creating collaborative cultures in highly fragmented HEIs.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that Kezar's [3] seven organizational features are vital for recognizing which structures and supports are needed to carry out SD work and be better prepared to meet the demands being placed on HEIs today. These structural components are augmented by other studies that outline best practice approaches, which can be implemented within a HEI to increase interdisciplinary collaboration [70]. Future research should include understanding the relationship between ecological legacy and collaborative cultures, and the correlation of the eight categories of SD within HEIs with the infrastructure offered by Kezar [3] and Roper [70] in order to offer more concrete ways of creating collaborative cultures in highly fragmented HEIs.…”
Section: Discussionmentioning
confidence: 99%
“…Everyone has access to a pool of experience. The business will reduce double handling and make the most of the teams' efforts (Roper, 2021). On the other hand, cross-departmental collaboration can only be done with the proper technical foundation to back it up.…”
Section: Encourage Collaboration Across Departmentsmentioning
confidence: 99%
“…leading to a reluctance to change (Carlgren & BenMahmoud-Jouini, 2022). The lack of collaboration and communication between different departments or agencies can create silos, hindering the flow of ideas and innovative practices (Roper, 2021).…”
Section: Introductionmentioning
confidence: 99%